Model for traditional freshmen orientation at the University of Wisconsin-La Crosse - Pein, Jill Daumler (My University, 1987)
The purpose of this paper was to propose a model for orienting traditional freshmen students at the University of Wisconsin-La Crosse. To understand the problem, a literature review of orientation practices from medieval to current times was undertaken with special emphasis on the history of orientation at UWL. Six goals for orientation resulted. The results of a survey sent to Orientation Directors at 61 schools in the NASPA 4E region, indicated the need to address academic issues in the orientation process. The need to use faculty, student personnel staff and student peers cooperatively as orientation leaders was indicated, as was the need to use small group experiences in the orientation process. Finally, student and staff satisfaction with the components of orientation, seems to be the primary indicator of their success. A three part model was developed which includes the following programs; Freshmen Advanced Registration, Freshmen Fall Orientation, and the Orientation Peer Advisor Program. The model is an ongoing process which continues through the first semester.
Keywords: University of Wisconsin--La Crosse -- Freshmen; College student orientation -- Wisconsin -- La Crosse